Edirneli Örfi'nin Leyla ve Mecnun'u - Gürgendereli, Müberra (Kitabevi, 2002)
The story of "Leyla ve Mecnun" which was written by an Iranian poet Nizami, has also been admired by Turkish poets and embroidered by more than thirty Turkish poets. One of these poets is the 18 th century poet Örfi from Edirne. The two known copies of "Leyla ve Mecnun" by Örfı are in Edirne and Erzurum. We made the text analysis of the mesnevi depending on these two copies. Later we examined this small mesnevi written by Örfi under the influence of the stories by Nizami, Cami, Hatifi, Nevai, Fuzuli and Halife according to its form and content features.
The Leyla ve Mecnun by Örfi from Edirne
Keywords: Örfi; Leyla ve Mecnun; Nizami; Edirne; Mesnevi